Commitments to the victims of international crimes for damage - خلف حسام عبدالامير; جبار رانيا صباح (Journal of Legal Sciences, 2021)
Granting rights, especially procedural, to victims before the International Criminal Court (ICC) is a fundamental departure from international criminal courts, whether (temporary or mixed military courts), and for the first time in the history of international criminal justice, victims can participate in reparations procedures before the Criminal Court. Where they can express their views and concerns at all stages of the proceedings, as the 1998 Rome Statute made the victim an active party in the court proceedings by recognizing a number of rights, such as the right to participate in the trial, the right to protection, and the right to legal representation, As well as the right to reparation or compensation.